A Family of Laminin α2 Chain-Deficient Mouse Mutants: Advancing the Research on LAMA2-CMD - Gawlik, Kinga I.; Durbeej, Madeleine (Frontiers in Molecular Neuroscience, 2020)
The research on laminin α2 chain-deficient congenital muscular dystrophy (LAMA2-CMD) advanced rapidly in the last few decades, largely due to availability of good mouse models for the disease and a strong interest in preclinical studies from scientists all over the world. These mouse models continue to provide a solid platform for understanding the LAMA2-CMD pathology. In addition, they enable researchers to test laborious, necessary routines, but also the most creative scientific approaches in order to design therapy for this devastating disorder. In this chapter we present animals belonging to the laminin α2 chain-deficient ‘dy/dy’ mouse family (dy/dy, dy2J/dy2J, dy3K/dy3K, dyW/dyW et al.) and a summary of the scientific progress they facilitated. We also raise a few questions that need to be addressed in order to maximize the usefulness of laminin α2 murine mutants and to further advance the LAMA2-CMD studies. We believe that research opportunities offered by the mouse models for LAMA2-CMD will continuously support our efforts to find a treatment for the disease.